A CONTRIBITION TO RESEARCH OF THE INFLUENCE OF DEGRADATION OF VEHICLE VIBRATION PARAMETERS ON THERMAL LOAD OF SHOCK ABSORBERS - Demić, Miroslav D. (Journal of Applied Engineering Science, 2013)
Summary: Dynamic simulation, based on modelling, has a significant role during to the process of vehicle development. It is especially important in the first stages of vehicle design, when relevant parameters are to be defined. In practice, it is commonly assumed that vehicle vibration parameters are invariable, what is basically not true. Many investigations have shown that vibration parameters degrade in service conditions, what consquently leads to the variation of dynamic characteristics of a vehicle. This paper attempts to indicate, on the basis of the preliminary results, a need to introduce these variations, caused by the thermal impact, in the early stages of vehicle design through the adequate vehicle modelling.
Keywords: Thermal load of shock absorbers; Vibration comfort; Degradation; Vibration parameters; VEHICLES